Strategi Dakwah Digital Habib Husein Ja’far Al-Hadar - Pahlevi, Reza (CV. ITTC INDONESIA, 2022)
Abstract: This research is entitled Habib Husein Ja'far Al-Hadar's Digital Da'wah Strategy by discussing the strategies used by Habib Jafar in preaching among young people. Habib Jafar came up with a da'wah that made young people as associates with a da'wah that was not monotonous and seemed more interesting. What da'wah strategy did Habib Husein Ja'far Al-Hadar use? What are the factors that influence the preaching of Habib Husein Ja'far Al-Hadar to get high viewers on the Jeda Nulis Youtube account? human engineering. The strategy used by Habib Husein Ja'far Al-Hadar is to build good credibility, attractive appeal, and have support from other institutions or media.